A low-level stress measurement method by integrating white light photoelasticity and spectrometry. (1st January 2018) - Sung, Po-Chi; Wang, Wei-Chung; Hwang, Chi-Hung; Lai, Guan-Ting
Highlights: Proposing low-level stress measurement technique by integrating photoelasticity and spectrometry. Deriving linear equations of transmissivity extremities by studying spectroscopy. Building 3D systematic relationship of transmissivity with stress and wavelength. Accurately obtaining linear equation of transmissivity extremity by regression. Obtaining stress without using stress-optic coefficient. Abstract: To face the increasing demand of residual stress measurement in many hi-tech industries, the integration of photoelasticity and advanced image acquisition equipment is a natural trend. With the integration of photoelasticity and spectrometry, the measurement capability of low-level stress and the stress in low birefringence materials can be enhanced. In fact, there is a significant correlation between the stress level and transmissivity spectrum. The key of the stress measurement method proposed in this paper is to find this scarcely explored correlation. By analyzing the periodic extinction phenomenon of isochromatic fringe pattern obtained from white light photoelasticity and the equation of transmissivity spectrum expressed in stress and wavelength, a three-dimensional (3D) systematic relationship of transmissivity with stress and wavelength can be established. By applying the 3D systematic transmissivity with stress and wavelength, the stress value can be determined directly from the transmissivity of the light transmitted through the polariscope. Moreover, when the proposed method is employed, the required parameters can be directly obtained from the database. There is no need to know the wavelength-dependent stress-optic coefficient beforehand. Glass, a very low birefringence material, was used to confirm the feasibility of the proposed method. Two regression approaches to search the transmissivity extremities were attempted to find the optimum systematic relationship.